Clinical Associations of Preoperative and Postoperative Serum CEA and Lung Cancer Outcome - Jiao, Zonglin; Cao, Shoubo; Li, Jianhua; Hu, Nan; Gong, Yinghui; Wang, Linduo; Jin, Shi (Frontiers in Molecular Biosciences, 2021)
BACKGROUND: Serum carcinoembryonic antigen (CEA), a classic tumour marker, is widely used in lung cancer in clinical practice. Nevertheless, few studies have elucidated the influence of dynamic changes in CEA in the perioperative phases, as a prognostic indicator, on lung cancer prognosis. METHODS: This retrospective cohort analysis included consecutive patients with stage I-III lung cancer who underwent curative resection between December 2010 and December 2014. The patients were grouped into 3 cohorts: group A included patients with normal preoperative CEA, group B included patients with elevated preoperative CEA but normal postoperative CEA, and group C included patients with elevated preoperative and postoperative CEA. Five-year overall survival (OS) was estimated by Kaplan-Meier analysis (log-rank test). Multivariate analyses were performed with Cox proportional hazard regression. RESULTS: A total of 1662 patients with stage I-III lung cancer were enrolled in our study. Patients with normal preoperative CEA had 15.9% and 20.1% better 3- and 5-year OS rates than the cohort with elevated preoperative CEA (p<0.001). Furthermore, group C had 36.0% and 26.6% lower 5-year OS rates (n=74, 32.4%) than group A (n=1188, 68.4%) and group B (n=139, 59.0%) (p<0.001). Group B had poorer OS than group A (p=0.016). For patients with different pathological TNM stages, subgroup analyses showed that group C had the shortest OS in stages I and II (p<0.05), and patients with a post-preoperative CEA increment had poorer OS than those without an increment (p=0.029). Multivariate analyses suggested that group C (HR=2.0, 95% CI, 1.5-2.7, p<0.001) rather than the group with normalized postoperative CEA (HR=1.2, 95% CI, 0.9-1.5, p=0.270) was an independent prognostic factor. In subgroup analysis of adenocarcinoma (ADC), survival analyses suggested that group C predicted a worse prognosis. Multivariate analysis of ADC indicated that group C was an independent adverse prognostic factor (HR=1.9, 95% CI, 1.4-2.7, p<0.001). CONCLUSIONS: Combined elevated preoperative and postoperative CEA is an independent adverse prognostic factor for stage I-III lung adenocarcinoma. Additionally, routine perioperative detection of serum CEA can yield valuable prognostic information for patients after lung cancer surgery. Keywords: lung cancer; carcinoembryonic antigen; prognosis